Contraceptive use and associated factors among women seeking induced abortion in Debre Marko's town, Northwest Ethiopia: a cross-sectional study - Lebeza Alemu; Yeshambel Agmus Ambelie; Muluken Azage (BMC, 2020)
Abstract Background Contraceptive utilization is a practice that helps individuals or couples to avoid unwanted pregnancy. Even though there is the widespread availability of contraceptives, induced abortion remains an alarming public health problem in Ethiopia. Nationally, more than a third (35%) of women seeking an induced abortion service had a previous history of abortion. Therefore, this study aimed to assess the history of contraceptive use and identify associated factors among women seeking an induced abortion service in Debre Marko's town, Ethiopia. Methods An institutional-based cross-sectional study was conducted from March 15 to May 15, 2019. The sample size was 416 and each health institution was proportionally allocated based on the previous 2 months of patient flow. Systematic random sampling was used to select the study participants. A structured questionnaire was used to collect the data. Data were entered by EPI-data and analyzed using SPSS version 23. Bivariate and multivariable logistic regression analyses were carried out. Model fitness was assured. Results The proportion of contraceptive use within the last 6 months before pregnancy was 41.3% among women seeking an induced abortion. Women who had good knowledge about contraceptives (AOR = 3.9; 95%CI: 2.36, 6.54), women who had a positive attitude about contraceptives (AOR=; 95%CI: 1.02, 2.56), women who had living children (AOR = 2.1; 95%CI; 1.04, 4.11), women who had frequent sexual practice (AOR = 2.5; 95% CI; 1.53, 4.21) and women discussed with their sexual partners about contraceptives (AOR = 1.9; 95%CI: 1.18, 3.18) were increase the odds of contraceptive use among women seeking an induced abortion. Conclusion Contraceptive use among women seeking an induced abortion was low despite the expected national goal of 55% contraceptive use in 2020. Having good knowledge and having a positive attitude on contraceptives, and having a discussion on contraceptives with sexual partner were increase the odds of contraceptive use. The intervention should focus on abortion seeking women to achieve their contraceptive needs and encourage sexual partner discussion about contraceptives to improve joint partner collective decision-making.